A Comparison on Prevalence of Hypertension and Related Risk Factors between Island and Rural Residents of Dalian City, China. (13th May 2019) - Liu, Baiting; Liu, Hainiang; Na, Rongmei; Li, Xiaofei; Li, Qianxiao; Chen, Libo; Tu, Wencheng; Hu, Jiahui; Cheng, Dong; Cao, Yalan; Li, Zhu; Fang, Weiyi; et al.
Abstract : This study aimed to compare the prevalence of hypertension between the island and rural residents in Dalian, China, and to explore associated risk factors of hypertension in order to provide evidence for the establishment of targeted strategy of hypertension prevention and treatment for island and rural residents. The modified MONICA questionnaire survey was performed on 7764 island and rural residents aged ≥40 years (including 2652 island residents and 5112 rural residents). Our data showed that totally weighted prevalence of hypertension was significantly higher in rural residents than in island residents (61.9% vs. 55.2%, P<0.001). Multivariate binary logistic regression analysis showed that older age, higher BMI, lower education level, and higher LDL-C and UA levels were independently associated with increased risk of having hypertension both in island and in rural residents. The weighted awareness rate (29.9% vs. 17.3%, P<0.001), treatment rate (51.4% vs. 28.5%, P<0.001), and control rate (36.3% vs. 24.0%, P=0.001) of hypertension were all significantly higher in island residents than those in rural residents. In conclusion, our survey shows that the epidemics of hypertension are extremely high in surveyed residents in island and rural areas of Dalian city, while awareness, treatment, and control rats of hypertension in these residents are much lower than the national level. The scenario is even worse in rural residents as compared with island residents of Dalian, China.